DPP3: From biomarker to therapeutic target of cardiovascular diseases - Ye, Peng; Duan, Wei; Leng, Yue-Qi; Wang, Yang-Kai; Tan, Xing; Wang, Wei-Zhong (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease is the leading cause of death globally among non-communicable diseases, which imposes a serious socioeconomic burden on patients and the healthcare system. Therefore, finding new strategies for preventing and treating cardiovascular diseases is of great significance in reducing the number of deaths and disabilities worldwide. Dipeptidyl peptidase 3 (DPP3) is the first zinc-dependent peptidase found among DPPs, mainly distributes within the cytoplasm. With the unique HEXXGH catalytic sequence, it is associated with the degradation of oligopeptides with 4 to 10 amino acids residues. Accumulating evidences have demonstrated that DPP3 plays a significant role in almost all cellular activities and pathophysiological mechanisms. Regarding the role of DPP3 in cardiovascular diseases, it is currently mainly used as a biomarker for poor prognosis in patients with cardiovascular diseases, suggesting that the level of DPP3 concentration in plasma is closely linked to the mortality of diseases such as cardiogenic shock and heart failure. Interestingly, it has been reported recently that DPP3 regulates blood pressure by interacting with the renin-angiotensin system. In addition, DPP3 also participates in the processes of pain signaling, inflammation, and oxidative stress. But the exact mechanism by which DPP3 affects cardiovascular function is not clear. Hence, this review summarizes the recent advances in the structure and catalytic activity of DPP3 and its extensive biological functions, especially its role as a therapeutic target in cardiovascular diseases. It will provide a theoretical basis for exploring the potential value of DPP3 as a therapeutic target for cardiovascular diseases.